Funkcje konsumpcji w krajach Unii Europejskiej - Utzig, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
In the paper estimation of consumption functions of the European Union’s countries assuming three forms of consumption functions were presented: 1. Simple consumption function in the form proposed by Keynes. 2. Consumption function consistent with the life-cycle hypothesis by Ando and Modigliani. 3. Consumption function consistent with the theory of permanent income of Friedman. Equations of the consumption were estimated on the basis of Eurostat macroeconomic data concerning years 1995–2007. In all the models marginal propensity to consume turned out to be statistically significant